2017
DOI: 10.1007/978-1-4939-6996-8_4
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Neuronal Synaptic Membranes by Sucrose Gradient Centrifugation

Abstract: Sucrose gradient centrifugation is a very useful technique for isolating specific membrane types based on their size and density. This is especially useful for detecting fatty acids and lipid molecules that are targeted to specialized membranes. Without fractionation, these types of molecules could be below the levels of detection after being diluted out by the more abundant lipid molecules with a more ubiquitous distribution throughout the various cell membranes. Isolation of specific membrane types where the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…We identified two brain-derived VLC-SFA products of ELOVL4, 28:0 and 30:0 as components of sphingolipids. Furthermore, membrane fractionation and lipidomic analysis (Hopiavuori et al, 2017c) of freshly dissected baboon hippocampus revealed a dramatic enrichment of both 28:0 and 30:0 in synaptic vesicle membranes relative to the other membrane fractions analyzed (Hopiavuori et al, 2017b) (Fig. 9A–E).…”
Section: Understanding the Role Of Elovl4 In The Cns; A Shift To In Vmentioning
confidence: 94%
“…We identified two brain-derived VLC-SFA products of ELOVL4, 28:0 and 30:0 as components of sphingolipids. Furthermore, membrane fractionation and lipidomic analysis (Hopiavuori et al, 2017c) of freshly dissected baboon hippocampus revealed a dramatic enrichment of both 28:0 and 30:0 in synaptic vesicle membranes relative to the other membrane fractions analyzed (Hopiavuori et al, 2017b) (Fig. 9A–E).…”
Section: Understanding the Role Of Elovl4 In The Cns; A Shift To In Vmentioning
confidence: 94%
“…We used a modified version of the protocol described by VanGuilder et al [ 37 , 38 ]; see [ 39 ] for details. Briefly, five major membrane fractions were isolated along with a starting homogenate (H) from freshly dissected baboon hippocampus: P1 (nuclear), P2 (cytoskeletal), P3 (neurosynaptosomal), PSD (post-synaptic density), and SV (synaptic vesicle).…”
Section: Methodsmentioning
confidence: 99%